Predicciones de cambios en el uso del suelo en el periodo 1986-2050 en la reserva biológica cerro plateado, parroquia nuevo paraíso, provincia de Zamora Chinchipe - Silva Cartuche, Blanca Nohely (2020)
The purpose of this study was to Prediction changes in land use by 2050 in the Cerro Plateado Biological Reserve, located in the new Paraíso parish of Zamora Chinchipe province, it is considered one of the areas with high concentration of biodiversity in southern Ecuador. The supervised classification of 1986, 2000 and 2018 years was obtained by the interpretation techniques of Landsat-5-7-8 and Sentinel-2 satellite images; in addition the Land Change Modeler (LCM) module of the TerrSet software was used to determine the losses, gains, net change of the different hedges and subsequently the deforestation rate. Finally, they were obtained the deforestation future scenarios were obtained through TerrSet software and the application of explanatory variables such as: digital elevation model, distance from roads, rivers and villages. During the 32 years of study, the main land use change was determined by the conversion from forest to grass, since for the first period 1986-2000 the deforestation rate was 0.057% and for the second period 2000-2018 was 0.13%. This depletion is due to the expansion of agricultural land, population growth and the construction of access roads which are considered the main sources of this change. For 2050, the estimated deforestation rate is 0.43%, which indicate an increasing deforestation trend. To sum up, the largest forest change was observed in the second period, where there was more anthropic intervention; however, the continued increase in deforestation put forest conservation at risk, for this reason deforestation monitoring with Landsat satellites is recommended. Keywords: Predictions, Landsat, land use change, Land Change Modeler